2015
DOI: 10.3892/or.2015.4208
|View full text |Cite
|
Sign up to set email alerts
|

Novel dihydrobenzofuro[4,5-b][1,8]naphthyridin-6-one derivative, MHY-449, induces cell cycle arrest and apoptosis via the downregulation of Akt in human lung cancer cells

Abstract: The anticancer properties of MHY-449, a novel dihydrobenzofuro[4,5-b][1,8]naphthyridin-6-one derivative, in various human cancer cell lines have been previously reported. The aim of the present study was to investigate the activities of MHY-449 on human lung cancer cells in order to elucidate its underlying molecular mechanisms of action. The result showed that MHY-449 treatment inhibited cell growth in a time- and concentration‑dependent manner. Specifically, MHY-449 induced cell cycle arrest at the S phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…Moreover, a significant accumulation of the tsFT210 cells at the G2/M phase was also observed after treatment for 17 h with ART [ 35 ]. Moreover, the increase in the percentage of XAN-treated cancer HeLa cells at the sub-G1 phase, compared to controls, was diagnostic of an increased number of apoptotic cells (sub-G1 population), as previously reported [ 36 ].…”
Section: Discussionsupporting
confidence: 80%
“…Moreover, a significant accumulation of the tsFT210 cells at the G2/M phase was also observed after treatment for 17 h with ART [ 35 ]. Moreover, the increase in the percentage of XAN-treated cancer HeLa cells at the sub-G1 phase, compared to controls, was diagnostic of an increased number of apoptotic cells (sub-G1 population), as previously reported [ 36 ].…”
Section: Discussionsupporting
confidence: 80%
“…Cyt-c can activate the caspase cascade after mitochondrial release, inducing the expression of the effector protein caspase-3, and activating cleavage of PARP protein to induce mitochondria-dependent apoptosis. The dynamic balance of Bcl-2/Bax also affects the occurrence of apoptosis [18]. In our study, cytisine caused an increase in expression levels of Cyt-c, BAD, cleaved caspase-3, and PARP protein and a decrease in Bcl-2 protein levels ( Figure 2D).…”
Section: Discussionsupporting
confidence: 51%
“…The AKT pathway has been considered to exert a crucial role in regulating cell growth, proliferation, survival, and motility ( 25 28 ). Our previous studies also revealed that sCLU suppressed HCC cell apoptosis induced by AKT inhibition ( 19 ).…”
Section: Resultsmentioning
confidence: 99%